PERTUMBUHAN WILAYAH KABUPATEN KEBUMEN BERDASARKAN POLA PASAR TANAH - , NOVI PRISTIANTI; , Ir. Prijono Nugroho D., MSP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Land is a important source for human life. Each living things need land to do their activities. The more raising citizens, the more request of land. the price of land is high because land area is absolut but it has highly requested. This condition happened in Kebumen Distict with 1.281,11 kilometer square area and its increasingly citizen. Land market pattern represent area growth. The aim of this research is to identify the kabupaten Kebumen developing direction based on shaped land market pattern. Market pattern is drawn in land sale date. Internal factors used to identify the patterns were width, size, topography, legal aspect, and zoning. On the other hands, the external factors were accessibility and infrastructure. Market pattern is visualized in tables, graphs, and maps. Based on the sum of land sale, land prices, and NJOP, land market pattern shaped shows the direction of the developing area in Kabupaten Kebumen. It leaned in the strategic area. Based on the land width, land market pattern shaped doesnât show the direction of the developing area in Kabupaten Kebumen. It can be said that external factors have great influence to define the direction of the developing area. Products of this research were showed developed area in Kabupaten Kebumen leaning in the nearest city center area.